Effects of lumbar myelography on subarachnoid pressure and cardiorespiratory parameters in healthy sheep - Minto, Bruno W. [UNESP]; Mesquita, Luciane R. [UNESP]; Souza, João A.l. [UNESP]; Bueno, Gabriela M. [UNESP]; Faria, Luís G. [UNESP]; Kawamoto, Fernando Y.k. [UNESP]; Yamada, Diego [UNESP]; Marques, Luis C. [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2021)
The purpose of this study was to evaluate the effects of lumbar myelography on subarachnoid pressure, cardiorespiratory parameters and pressure-volume index in sheep. Eight sheep were evaluated. The animals were submitted to puncture of the cisterna magna for monitoring of subarachnoid pressure (SaP). Lumbar myelography was performed through applying Iohexol (0.4mL/kg). ToC, PAS, PAD, MAP, InspISO, FeISO, SaP and CPP were recorded immediately after anesthetic stabilization (M0), during lumbar puncture (M1), and two, four and six minutes after contrast application (M2, M3 and M4, respectively). Blood pressure initially increased, then decreased, returning to basal level, similarly observed for InspISo and FeISo. The SaP rose initially thereafter remaining stable. Despite of the effect on subarachnoid pressure, lumbar myelography can be considered safe in sheep.

O objetivo foi avaliar os efeitos da mielografia lombar na pressão subaracnóidea, parâmetros cardiorrespiratórios e índice pressão-volume em ovinos. Oito ovelhas foram avaliadas. Os animais foram submetidos à punção da cisterna magna para monitoramento da pressão subaracnoidea (SaP). A mielografia lombar foi realizada com a aplicação de Iohexol (0,4mL/kg). Os momentos estudados foram: imediatamente após a estabilização anestésica (M0), durante a punção lombar (M1), dois, quatro e seis minutos após a aplicação do contraste (M2, M3 e M4, respectivamente), para avaliar as seguintes variáveis: ToC, PAS, PAD, MAP, InspISO, FeISO, Sap e CPP. A pressão arterial aumentou inicialmente, depois diminuiu, retornando aos valores iniciais, padrão também observado para o InspISo e o FeISo. O SaP subiu inicialmente, posteriormente, permanecendo estável. A mielografia lombar, apesar de influenciar a pressão subaracnoidea, pode ser considerada segura em ovinos.
Efeitos da mielografia lombar na pressão subaracnoidea e nos parâmetros cardiorrespiratórios em ovelhas saudáveis
Keywords: Lumbar; myelography; subarachnoid pressure; cardiorespiratory parameter; sheep; neuroradiology; intercranial pressure; ovine; pressure-volume index; Mielografia; lombar; pressão subaracnóidea; cardiorrespiração; ovelhas neurorradiologia; pressão intracraniana; ovinos; índice volume-pressão